Lucht : een thematentoonstelling. (Schiedam : Stedelijk Museum Schiedam, 1978)
Andringa, Hans ; Berserik, Hermanus ; Bertholo ; Boezem, Marinus ; Van Bohemen, Kees ; Van Bommel, Koos ; Botschuyver, Theo ; Claassen, Johan ; Daubigny, Charles-François ; Eames, Dickon ; Engels, Pieter ; Fioole, Piet ; Fischer, Anne Marie ; Gabriel, P.J.C. ; Gamarra, Jose ; Gillesse, Nico ; etc.
Lucht : een thematentoonstelling, Stedelijk Museum Schiedam, 25 juni - 28 augustus 1978
boek